The geopolitics of energy system transformation: A review. Issue 7 (29th June 2021) - Blondeel, Mathieu; Bradshaw, Michael J.; Bridge, Gavin; Kuzemko, Caroline
Abstract: In 2009, Geography Compass published a paper on 'The Geopolitics of Global Energy Security' that reviewed research on the key geographical factors influencing the secure and affordable supply of energy resources. Now, just over a decade later, the energy landscape is undergoing a dramatic transformation, and the focus is no longer on fossil fuel scarcity. Rather, this is an age of fossil fuel abundance and the emphasis is on the need to decarbonise the global energy system, constrain the production of fossil fuels and accelerate the deployment of low‐carbon energy technologies. We conceive energy system transformation as a twofold process: a set of 'high‐carbon' energy transitions related to phasing out fossil fuel consumption, 'low‐carbon' energy transitions related to the emergence of new renewable energy and other low‐carbon technologies. This paper reviews the past decade's research that examines the nature and pace of energy system transformation, as well as that which identifies a range of geopolitical challenges associated with these two transitions. The paper concludes by advocating for a 'whole systems' approach to energy geopolitics that captures the critical interactions between the two transitions in a global framework.